Going against global marriage trends: the declining age at first marriage in Indonesia - Dommaraju, Premchand (2023)
Marriage is a key marker in the transition to adulthood across much of Asia. Globally, early marriages have declined, and marriage age has increased. This study examined changes in marriage timing for Indonesian women between 1965 and 2016 using multiple data sources, including registration, censuses, and surveys, and employed a robust methodology. The findings show that there was a steady decrease in the probability of first marriage between 1965 and 1990. But this trend reversed in the early 2000s, with an increase in the likelihood of marriage. Women with lower education showed a stall in the decline of early marriage during this period, while the probability of marriage by age 24 increased among women with higher education. The educational disparities in marriage timing have persisted, but the gap between women with completed secondary and lower education has narrowed, while the difference between those with completed secondary and higher education has remained consistent. These findings highlight the influence of both short-term events and long-term changes in gender ideologies, family values, moral norms, and the rise of Islamization on marriage timing in Indonesia.